The Italian version of the unified theory of acceptance and use of technology questionnaire: a pilot validation study - D’Iorio, Alfonsina; Garramone, Federica; Rossi, Silvia; Baiano, Chiara; Santangelo, Gabriella (Frontiers in Robotics and AI, 2025)
BackgroundThe Unified Theory of Acceptance and Use of Technology is a self-rated questionnaire to assess twelve constructs related to the level of acceptance of a robot, consisting of 41 items rated on a 5-point Likert scale. The aim of the study was to conduct a preliminary evaluation of the psychometric properties of the Italian version of the UTAUT (I-UTAUT) in a sample of Italian healthy subjects (HCs).Materials and methods30 HCs underwent the I-UTAUT to assess its comprehensibility. Reliability and divergent validity of the I-UTAUT were evaluated in a sample of 121 HCs, who also underwent the Montreal Cognitive Assessment (MoCA).ResultsThe final I-UTAUT version was easily comprehensible. There were no missing data, no floor and ceiling effects. Contrarily to the original version, the Principal Components Analysis suggested a seven-component structure; Cronbach’s alpha was 0.94. The I-UTAUT score did not correlate with MoCA.ConclusionThe I-UTAUT represented a reliable and valid questionnaire to identify the level of acceptance of robotics technology in Italian healthy sample.